Potential feminization of Red Sea turtle hatchlings as indicated by in situ sand temperature profiles. Issue 10 (4th September 2020) - Tanabe, Lyndsey K.; Ellis, Joanne; Elsadek, Islam; Berumen, Michael L.
Abstract: Climate change poses a serious threat to species that demonstrate temperature‐dependent sex determination, including marine turtles. Increased temperatures can result in highly female‐skewed sex ratios and decreased hatching success. The pivotal temperature that delineates hatchling sex ratios is commonly considered to be 29.2°C, but whether this threshold applies to turtles in the Red Sea region has not been tested in situ. For all species of marine turtles, there is a supposed thermal range of 25–33°C in which egg incubation is successful, with prolonged temperatures above 33°C resulting in morphological abnormalities and hatchling mortality. Sand temperature data were collected from May–September 2018 from the average nesting depth of hawksbill ( Eretmochelys imbricata ) and green turtles ( Chelonia mydas ) at five study sites. We calculated the expected sex ratio based on a maximum likelihood model. The sand temperature profile at four of the sites exceeded the pivotal temperature (29.2°C) throughout the study duration, which suggests feminization of turtles could be occurring; however, the pivotal temperature in this region still needs to be empirically confirmed. The percentage of days with sand temperature exceeding the maximum thermal threshold between June 3, and September 16, 2018, was site‐specific rather than determined by latitudinal temperature gradients, and ranged between 0 and 100% of days. Maximum temperature recordings were as high as 36.0 and 35.3°C at 30 and 50 cm depth, respectively. Nesting sites in the Red Sea region could already be exceeding the thermal limits and may be particularly vulnerable to rising temperatures. Sites with lower sand temperatures, such as Small Gobal Island, may represent priority areas for conservation efforts. Alternatively, local adaptation may be a reality under extremely warm conditions, thus, further research into the thermal tolerance of hatchlings in the region could provide insight on how they might adapt to future climate change. Abstract : Sand temperature data were collected from May to September 2018 from the average nesting depth of hawksbill ( Eretmochelys imbricata ) and green turtles ( Chelonia mydas ) at five study sites in the Red Sea. The sand temperature profile at four of the sites exceeded the pivotal temperature (29.2°C) throughout the study duration, which suggests feminization of turtles could be occurring. Sites with lower sand temperatures (and lower risk of feminization) may represent priority areas for conservation efforts, particularly in regions facing imminent coastal development.